2020
DOI: 10.1038/s41420-020-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

TGR5-HNF4α axis contributes to bile acid-induced gastric intestinal metaplasia markers expression

Abstract: Intestinal metaplasia (IM) increases the risk of gastric cancer. Our previous results indicated that bile acids (BAs) reflux promotes gastric IM development through kruppel-like factor 4 (KLF4) and caudal-type homeobox 2 (CDX2) activation. However, the underlying mechanisms remain largely elusive. Herein, we verified that secondary BAs responsive Gprotein-coupled bile acid receptor 1 (GPBAR1, also known as TGR5) was increased significantly in IM specimens. Moreover, TGR5 contributed to deoxycholic acid (DCA)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
(65 reference statements)
1
18
0
Order By: Relevance
“…BAs can enhance caudal-related homeobox family 2 (CDX2) and mucin 2 (MUC2) expression via FXR/NF-κB signaling [ 176 , 177 ] and cyclooxygenase-2 (COX-2) expression via induction of SHP [ 178 ], all promoting gastric intestinal metaplasia. Acidic bile salts can induce telomerase activity in a c-Myc-dependent fashion [ 179 , 180 ], while DCA can induce the metaplastic phenotype of gastric cancer cells [ 181 ] (see Tables 6 and 7 ). TGR5 is a key factor in BA-induced gastric metaplasia via HNF4α [ 181 ], EGFR and mitogen-activated protein kinase (MAPK) [ 182 ] activation and promotes EMT in gastric carcinoma cells [ 183 ].…”
Section: Effects Of Bile Acids In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…BAs can enhance caudal-related homeobox family 2 (CDX2) and mucin 2 (MUC2) expression via FXR/NF-κB signaling [ 176 , 177 ] and cyclooxygenase-2 (COX-2) expression via induction of SHP [ 178 ], all promoting gastric intestinal metaplasia. Acidic bile salts can induce telomerase activity in a c-Myc-dependent fashion [ 179 , 180 ], while DCA can induce the metaplastic phenotype of gastric cancer cells [ 181 ] (see Tables 6 and 7 ). TGR5 is a key factor in BA-induced gastric metaplasia via HNF4α [ 181 ], EGFR and mitogen-activated protein kinase (MAPK) [ 182 ] activation and promotes EMT in gastric carcinoma cells [ 183 ].…”
Section: Effects Of Bile Acids In Cancersmentioning
confidence: 99%
“…Acidic bile salts can induce telomerase activity in a c-Myc-dependent fashion [ 179 , 180 ], while DCA can induce the metaplastic phenotype of gastric cancer cells [ 181 ] (see Tables 6 and 7 ). TGR5 is a key factor in BA-induced gastric metaplasia via HNF4α [ 181 ], EGFR and mitogen-activated protein kinase (MAPK) [ 182 ] activation and promotes EMT in gastric carcinoma cells [ 183 ]. TGR5 is overexpressed in gastrointestinal adenocarcinomas, and moderate to strong TGR5 staining is associated with decreased patient survival [ 184 ].…”
Section: Effects Of Bile Acids In Cancersmentioning
confidence: 99%
“…5,6 However, it is noteworthy that both gastric IM and Barrett's metaplasia of the esophagus, another type of IM, are the result of bile acid reflux. 7,8 This strongly suggests a key regulatory role of bile acid reflux in IM.…”
Section: Introductionmentioning
confidence: 97%
“…In adults, HNF4α is expressed in the colon and small intestine, not in the gastric mucosa, but HNF4α mediated by the P1 promoter can be observed in gastric IM tissues [ 41 ]. Zhen et al found that bile reflux activated the TGR5–ERK1/2 pathway after induction of HNF4α expression, thus upregulating the expression of CDX2 [ 42 ]. Wang et al found that bile acids promoted the development of gastric IM through HNF4a/HDCA6/CDX2 pathway in vivo and in vitro [ 43 ].…”
Section: Mechanism Of Gastric Im Induced By Bile Acidmentioning
confidence: 99%
“… [ 109 ] DCA TGR5 tissues, cell lines BAs treatment could activate TGR5–ERK1/2 pathway following induction of HNF4α expression, which further promoted metaplasia markers expression through direct regulation of KLF4 and CDX2. [ 42 ] …”
Section: Bile Acid Receptorsmentioning
confidence: 99%